Comparison of the Effect of Toothbrushing Education Via Video, Lecture and Pamphlet on the Dental Plaque Index of 12-Year-Old Children - Javad Ramezaninia; Mohammad Mehdi Naghibi Sistani; Zohreh Ahangari; Hemmat Gholinia; Iman Jahanian; Samaneh Gharekhani (MDPI AG, 2018)
The aim of this study was to compare the effect of different modes of toothbrushing education (lecture, video and pamphlet) on the dental plaque index (PI) of adolescents. The cluster randomized intervention was performed on 128 participants aged 12 years, who were allocated into four groups based on the type of intervention. Group 1: no intervention; and groups 2, 3, 4: education via lecture, video, and pamphlet, respectively (n = 32). Their plaque index was measured at the baseline, 24 h and two months later. Data were analyzed by repeated measures analysis of variance (ANOVA), one-way ANOVA, independent and paired t-test. The plaque indices of groups 2, 3, 4 at 24 h (p values < 0.001) and two months (p values < 0.001) showed a significant reduction when compared to the baseline. The lowest PI score was observed in the pamphlet, video and lecture groups at 24 h, respectively. After 2 months, the lowest score of PI was measured in lecture, video and pamphlet groups, respectively; however, these differences were non-significant. Therefore, toothbrushing education via lecture, video and pamphlet reduced the dental plaque index with the same effectiveness.